RISK ANALYSIS AND FRAUD MITIGATION IN THE GOODS AND SERVICES PROCUREMENT CYCLE IN THE NORTH MINAHASA REGENCY GOVERNMENT - Steven Endru Pandean; Recky H. E. Sendouw; Meidy S. S. Kantohe (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze fraud risks, formulate mitigation strategies, and map the most prevalent forms of fraud in the procurement cycle of goods and services within the Government of North Minahasa Regency for the fiscal years 2022–2025. Employing a descriptive qualitative approach, data were collected through semi-structured interviews with five key informants (Head of Procurement Division, LPSE Operator, Regency Inspector, and two Commitment-Making Officials from the Public Works and Health Offices), supplemented by field observation and secondary document analysis. The findings address three core focuses: (1) The highest fraud vulnerability concentrates in the planning stage, particularly in immature RUP preparation, technical specifications, and Owner's Estimate Price (HPS), exacerbated by rigid year-end budget absorption targets and limited human resource capacity; (2) The five COSO principles have been formally adopted through the Government Internal Control System (SPIP), yet operational implementation remains inconsistent due to formalistic leadership commitment, non-participatory risk assessments, and monitoring mechanisms lacking consequential follow-up; (3) Three dominant fraud clusters emerge: upstream manipulation (inflated HPS and vendor-tailored specifications), downstream deviations (substandard materials and unreported volume reductions), and payment irregularities (full disbursements prior to 100% physical completion).